Lipoprotein macroaggregates in bronchoalveolar lavage fluid from patients with diffuse interstitial lung disease: comparison with idiopathic alveolar lipoproteinosis. Issue 2 (February 1988) - Haslam, P L; Hughes, D A; Dewar, A; Pantin, C F
Abstract : Lipoprotein macroaggregates were present in cytocentrifuge preparations of bronchoalveolar lavage fluid from four patients with diffuse lung diseases other than idiopathic alveolar lipoproteinosis. In three patients the primary diagnosis was cryptogenic fibrosing alveolitis and in one sarcoidosis. We confirmed the presence of large multilamellar aggregates of lipoprotein by ultrastructural examination in patients with both interstitial lung disease and idiopathic alveolar lipoproteinosis. The small lamellar bodies and amorphous debris found in idiopathic alveolar lipoproteinosis were rare in the patients with interstitial lung disease. The lavage fluid from patient with interstitial lung disease did not show the substantial alterations in phospholipid composition that were seen in lavage fluid in idiopathic alveolar lipoproteinosis. These ultrastructural and biochemical features may help to distinguish idiopathic from other causes of alveolar lipoproteinosis, particularly at an early stage, when differential diagnosis may be difficult.